Manfaat gerakan sholat pada fisiologis tubuh - Ardiansyah, Fahrus Surya (Maliki Interdisciplinary Journal, 2025)
Worship in Islam is a crucial aspect for its followers, with prayer being a fundamental practice that consists of a series of words and actions, starting with the Takbir and including bowing, standing, prostration, sitting between prostrations, and concluding with greetings. It holds special significance as the Prophet Muhammad received this command directly from Allah during the Isra’ Mi’raj. Prayer serves as a remedy for the soul, addressing various inner struggles and providing tranquility to those who practice it, fostering gratitude for life’s experiences while creating a dialogue between Allah and His servants. Additionally, prayer acts as a means of purification from intentional or unintentional sins, uniting the soul and mind in the pursuit of closeness to God. Moreover, the benefits of prayer extend beyond spiritual well-being; it also promotes physical health, as the movements involved contribute to strengthening bones, blood vessels, and muscles. Thus, prayer is not only a source of spiritual solace but also a vital practice for overall health and wellness human body, it is said to be a means of health for the human body, namely in prayer there are movements that play a role in healthy bones, blood vessels and muscles